2017
DOI: 10.1371/journal.pbio.2004044
|View full text |Cite
|
Sign up to set email alerts
|

Sonic Kayaks: Environmental monitoring and experimental music by citizens

Abstract: The Sonic Kayak is a musical instrument used to investigate nature and developed during open hacklab events. The kayaks are rigged with underwater environmental sensors, which allow paddlers to hear real-time water temperature sonifications and underwater sounds, generating live music from the marine world. Sensor data is also logged every second with location, time and date, which allows for fine-scale mapping of water temperatures and underwater noise that was previously unattainable using standard research … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 19 publications
(15 reference statements)
0
17
0
Order By: Relevance
“…Huge stretches of the world's tropical and subtropical coastline are populated with surfing beaches [19], and although there are seasonal changes in the frequency of participation, surfing occurs all year around even in cold and dark winter months at high latitudes. There is a huge potential to use surfers to help increase the coverage of nearshore ocean observations like temperature, using the types of approaches tested here, which can be easily expanded to other aquatic recreational activities (e.g., diving, kayaking) and to other environmental indicators of aquatic health, such as ocean acidity and water quality [20][21][22][23][24][25][26].…”
Section: Future Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Huge stretches of the world's tropical and subtropical coastline are populated with surfing beaches [19], and although there are seasonal changes in the frequency of participation, surfing occurs all year around even in cold and dark winter months at high latitudes. There is a huge potential to use surfers to help increase the coverage of nearshore ocean observations like temperature, using the types of approaches tested here, which can be easily expanded to other aquatic recreational activities (e.g., diving, kayaking) and to other environmental indicators of aquatic health, such as ocean acidity and water quality [20][21][22][23][24][25][26].…”
Section: Future Recommendationsmentioning
confidence: 99%
“…New evidence has suggested that environmental monitoring in the nearshore could be drastically improved by harnessing vast numbers of citizens who partake in marine recreational sports [19]. To date, there have been studies looking at the use of divers [20][21][22], fishermen [23], stand-up paddle boarders [24], kayakers [25], sailors [26], and surfers [27,28]. Measurements of water temperature (both at the surface and subsurface) have been a target of many of these studies, for two reasons: (1) temperature sensors are relatively cheap, small, and accurate, and consequently fairly easy to integrate into watersports equipment; and (2) water temperature is considered by the Global Climate Observing System as an Essential Climate Variable (ECV) [29,30] and by the Intergovernmental Panel on Climate Change (IPCC) as a key driver of climate change impacting coastal systems [31].…”
Section: Introductionmentioning
confidence: 99%
“…Fine-scale mapping of underwater sound is particularly novel. Underwater sound is usually collected using sensors attached to the seabed, drifting devices, or towed sensors on motored research vessels (Griffiths et al 2017). The seas around Cornwall have been modelled to have high levels of underwater noise (Farcas et al, 2020).…”
Section: Data Interpretationmentioning
confidence: 99%
“…The equipment is designed to fit onto any model of kayak. The Sonic Kayak Version 1 (Griffiths et al 2017) was equipped with temperature sensors and a hydrophone, recording the water temperature every second and underwater sound continuously, together with the GPS coordinates, time and date. The data is also sonified in real-time through an on-board speaker, allowing the paddler to hear the data as it comes in and to follow interesting occurrences, for example temperature gradients (sonification the process of conveying information by using non-speech sounds; Dubus & Bresin 2013, Hermann et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation